THE ROLE OF CLUSTER AND INVESTMENT IS THE FUTURE OF BUSINESS (World Economics and Finance Bulletin, 2022)
The article briefly describes the reforms carried out in the field of clusters in the Republic of Uzbekistan, as well as the benefits given to business entities forming clusters. In addition, there are recommendations for solutions to problems and deficiencies in business legislation related to the cluster system
Keywords: cluster; integration; innovation